A visible light illumination assistant Li-O2 battery based on an oxygen vacancy doped TiO2 catalyst. (10th February 2022) - Zhang, Li; Bai, Xiaoming; Zhao, Guangyu; Shen, Xiaojie; Liu, Yufei; Bao, Xiyang; Luo, Jing; Yu, Liping; Zhang, Naiqing
Abstract: TiO2 is regarded as one of the most stable catalysts for Li-O2 battery cathodes, however, the inert surface and weak conductivity limit its catalytic ability. In the present work, a visible light assistant electrode-process on an oxygen vacancy doped TiO2 (TiO2-δ ) catalyst is proposed to promote its performances in Li-O2 batteries. The TiO2-δ is prepared by an insufficient oxidation on Ti2 O3 through a hydrothermal process and subsequent heat-treatment, and this method guarantees the homogeneous distribution of oxygen vacancies in obtained TiO2-δ catalysts. The TiO2-δ possess a narrow bandgap, leading to a visible light adsorption, which leads to remarkable suppression on overpotential under illumination by xenon lamp in Li-O2 batteries. The electrochemical measurements indicate that, the illumination can obviously enhance the catalytic currents and reduce the electrochemical reaction impedance, and these contributions are responsible for the overpotential decrease. The in-situ gas chromatography is used for inspecting the oxygen flow of a cyclic battery, and the results reveal that, the illumination results in apparent increase in oxygen consumption/evolution in discharge/charge processes. We suggest the photo-induced electrons/vacancies on catalyst surface in discharge/charge processes promote the performances and reversibility of Li-O2 batteries.